Densidades de semeadura e reguladores de crescimento afetando o trigo - Hilgemberg, Pâmella (2010)
A correct management with lower costs in the crop can make a difference when one considers the maximization of yield for area of wheat crop management techniques should be adjusted to provide the greater profitability for producers of wheat. The aim of this study was to evaluate the effect of growth regulators and plant densities in three wheat cultivars. The experiments were deployed Farm School Capão da Onça in 2008, winter season. The treatments were sowing densities (150, 300, 450, 600, 750 and 900 seeds m-2) and with or without the growth regulator trinexapac-ethyl, in cultivars BRS208 and OR1. In the cultivar Safira, the treatments were six sowing rates (150, 300, 450, 600, 750, 900 seeds m-2) and regulators, trinexapac-ethyl and cycocel & ethepon. In all experiments, the regulators were applied between 1˚ and 2 ˚ node visible. Increasing the plant population decreased the number of tillers per plant, leaf area per plant, n ˚ green leaves per plant mother and increased productivity for the cultivars safira and OR1. In the experiments did not observe the presence of lodging, even in the cultivar safira, more susceptible. To cultivate safira observed an effect of regulators in the length of flag leaf, and to cultivate OR1, trinexapac-ethyl affected the width of the flag leaf. In the cultivar safira saw the effect of regulators in the reduction in height, which occurred specifically in 2 ˚, 3˚ and 4˚ internodes. The use of growth regulators in the experiments gave a decrease of plant height, for and the cultivar safira, regulators contributed to higher productivity, which was not observed OR1 and BRS208.